Delphi case: Sharing of clinical experiences for improvement in the treatment of chronic venous disease - Camporese, Giuseppe; Aloi, Teresa Lucia; Santoliquido, Angelo (Frontiers in Cardiovascular Medicine, 2022)
Chronic venous disease (CVD) is a common condition with major health consequences that is associated with poor long-term prognosis, significant socioeconomic impact, disabling symptoms and reduced quality of life. To provide a novel evidence-based approach in the management of CVD, a consensus process (“Delphi Case”) following a first Delphi Consensus was conceived. With a real-life fashion analysis, a steering committee formed by 3 expert leaders on chronic venous disease drove a panel of 77 expert Italian angiologists/vascular surgeons along a collegial discussion, integrating data coming from the guidelines recommendations of different Vascular Scientific Societies with the consensus agreement statements gathered from the first Delphi Consensus, and with data coming from the discussion of few statements in which there was disagreement. From July 15 to October 16, 2020, demographic, anamnestic, objective and therapeutic data coming from a total of 2275 patients were collected by the experts panel using a predefined case report form. The results of this second consensus provided a real-life picture of CVD management in the Italian population and clearly showed that a tailored therapeutic approach together with an appropriate lifestyle (e.g. diet, physical activity, weight loss) must be considered as the milestones for the CVD-related signs and symptoms clinical improvement in daily clinical practice. An evaluation of the adherence and of the efficacy of the prescribed pharmacological and compressive treatment in a medium-long term follow-up of the study population has been planned as the last step of this course and will be object of a future final publication.